A cross-sectional, mixed methods examination of a modified "Flipped Classroom" pedagogy: The "Sandwich Approach". (7th April 2018) - Hoepner, Jerry; Hemmerich, Abby
Abstract : The "Flipped Classroom" has garnered much popularity as an instructional pedagogy over the past several years. At times, popular press and less empirical descriptions have superseded data driven descriptions of the technique. Further, many of the publications, which describe the flipped classroom approach, provide limited information about implementation or a vague overview of the principle. Nonetheless, the approach has thrived and is used broadly given gains in engagement and academic performance reported in a few key investigations. Several shortcomings have been identified but not evaluated systematically, in terms of potential solutions. This paper attempts to summarise previous empirical research findings, describe a modified version of the pedagogy referred to as the "sandwich approach, " and provide detailed information regarding implementation. A multi-year, cross-sectional, and mixed qualitative-quantitative design was employed to analyse comparisons of traditional versus flipped versus sandwich pedagogies in an undergraduate neuroanatomy course. Variables included student performance, influence of each pedagogy on student confidence, and student perceptions regarding each pedagogy. In quantitative comparisons of final grades, the sandwich approach out-performed traditional instruction . Student confidence ratings were generally better in the flipped contexts, as opposed to traditional. Qualitative analyses compared barriers and facilitators across pedagogies. Perceived barriers were highest for the flipped classroom approach, whereas barriers were lowest for the sandwich pedagogy and facilitators were the highest for the sandwich approach. Previous evidence suggested that the flipped classroom approach improved grade performance but was perceived less favourably by students. The sandwich approach appears to improve grade performance at a level equivalent or exceeding flipped classroom approach, while improving student perceptions. Since student perceptions are likely related to their motivation and engagement, addressing concerns identified in previous research regarding student perceptions within the flipped classroom approach is an important finding.